Ministerial decree No. 95/2016 Amending Some Provisions of the Executive Regulation of the Capital Market Law Issued as per Decree of the Minister of Economy and Foreign Trade No. 135 of the year 1993 = قرار وزاري رقم 95 لسنة 2016 بتعديل بعض أحكام اللائحة التنفيذية لقانون سوق رأس المال الصادرة بقرار وزير الاقتصاد والتجارة الخارجية رقم 135 لسنة 1993 / Minister Prime. - Egypt. Minister Prime. (2025)
Ministry of Investment Decree no. 95 of the year amending some provisions of the executive regulations of the capital market law issued as per decree of the minister of economy and Foreign trade no. 135 of the year 1993 وزارة الاستثمار قرار رقم 95 لسنة 2016 بتعديل بعض أحكام اللائحة التنفيذية لقانون رأس المال اصلادرة بقرار وزير الاقتصاد والتجارة الخارجية رقم 135 لسنة 1993